Evaluation of cognitive function in patients with type 2 diabetes mellitus - ANANDHALAKSHMI SWAMINATHAN; PREETHI KRISHNAN; KUMAR JS; THIRUNAVUKARASU MANICKAM (International Journal of Pharma and Bio Sciences, 2018)
Diabetes mellitus (DM) is a global health problem with increased risk of complications affecting multiple organ systems. The effect of diabetes on kidneys, heart, retina and peripheral nerves have been studied but the effect on central nervous system has not been explored much. Our aim is to compare the cognitive function between diabetics and non-diabetics and to determine the effect of glycemic control and duration of diabetes on cognitive function. This cross-sectional study involved 100 Type-2 diabetic patients attending the diabetology outpatient department of SRM Medical College Hospital and Research Centre aged between 40 and 60 years and 100 age-matched non-diabetic subjects as controls. Subjects with psychiatric illness, liver dysfunction, thyroid disorder, type I diabetes mellitus, hypertension, history of previous head injury, stroke, epilepsy etc. were excluded from the study. After history taking and clinical examination, glycosylated haemoglobin (HbA1c), fasting and postprandial blood glucose levels were tested and the cognition was assessed by Folstein Mini Mental State examination (MMSE). We found that the mean MMSE score was significantly decreased among diabetics when compared to non-diabetics. Also the mean MMSE score was significantly decreased in diabetics with HbA1c >7%, and in diabetics with >10 years duration of diabetes. Diabetic patients have a decreased cognition as compared to the non diabetics and the cognition was significantly decreased in diabetics with poor glycemic control and those having a longer duration of diabetes.